THERMO-CATALYTIC REFORMING OF GENERAL WASTE TO PRODUCE BIOFUELS - Onyishi, Hillary Onyebuchi; Neidel, Johannes; Daschner, Robert; Franke, Matthias; Apfelbacher, Andreas; Hornung, Andreas (European Biomass Conference and Exhibition Proceedings, 2022)
This work investigates the feasibility of extracting biofuels from general waste through the novel thermo-catalytic reforming (TCR®) technology. Two feedstocks (Up-Sieve Material and Grey Compost) supplied from Risorse Ambiente Palermo (RAP) are studied. They are shredded, pelletised and characterised. The proximate analyses show the Up-Sieve feed has a higher heating value (HHV) of 17.6 MJ/kg with an ash content of 19.60 wt.%, while the Grey Compost feed has a HHV of 11.5 MJ/kg and an ash content of 40.16 wt.%. The results of the TCR® experiments on both feeds show that the Up-Sieve feed has more gas and oil yields while the Grey Compost has more char yield. The results from the characterisation of the oils and chars from both feeds show the oils have HHVs of 38.2 MJ/kg and 37.0 MJ/kg while the chars have HHVs of 13.6 MJ/kg and 5.7 MJ/kg respectively. Except for the char from the Grey Compost (with the 5.7 MJ/kg HHV), the products can be applied directly as biofuels due to their sufficient calorific values. By and large, the successful extraction of biofuels from general waste is a huge step in waste management and environmental protection.
CRIS-Team Scopus Importer:2022-12-02
Keywords: biofuels; thermo-catalytic reforming; thermochemical conversion; waste